Obstructive sleep apnoea and related comorbidities in incident idiopathic pulmonary fibrosis. Issue 6 (8th June 2017) - Gille, Thomas; Didier, Morgane; Boubaya, Marouane; Moya, Loris; Sutton, Angela; Carton, Zohra; Baran-Marszak, Fanny; Sadoun-Danino, Danielle; Israël-Biet, Dominique; Cottin, Vincent; Gagnadoux, Frederic; Crestani, Bruno; et al.
The objectives of this prospective study were: 1) to determine the prevalence and determinants of obstructive sleep apnoea (OSA) in patients with newly diagnosed idiopathic pulmonary fibrosis (IPF); 2) to determine whether OSA was associated with cardiovascular disease (CVD) as well as increased oxidative stress and levels of IPF biomarkers in the blood. A group of 45 patients with newly diagnosed IPF attended polysomnography. The prevalence of CVD and the severity of coronary artery calcification were investigated by high-resolution computed tomography. The levels of 8-hydroxydeoxyguanosine (8-OH-DG) and various IPF biomarkers in the blood were compared between patients with no or mild OSA (apnoea–hypopnoea index (AHI) <15 events·h −1 ), with moderate OSA (15 ≤AHI <30 events·h −1 ) and with severe OSA (AHI ≥30 events·h −1 ). The prevalence of moderate-to-severe OSA and severe OSA was 62% and 40%, respectively. AHI did not correlate with demographic or physiological data. All patients with severe OSA had a medical history of CVD, versus 41.2% and 40% of those with no or mild OSA, or with moderate OSA, respectively (p<0.0001). Ischaemic heart disease (IHD) and moderate-to-severe coronary artery calcifications were strongly associated with severe OSA. The 8-OH-DG and matrix metalloproteinase-7 serum levels were significantly increased in the severe OSA group. Moderate-to-severe OSA is highly prevalent in incident IPF and severe OSA is strongly associated with the presence of CVD, particularly IHD. Severe sleep apnoea syndrome is associated with cardiovascular disease in incident idiopathic pulmonary fibrosis http://ow.ly/9GTv30bgIOR